2021
DOI: 10.24272/j.issn.2095-8137.2021.224
|View full text |Cite
|
Sign up to set email alerts
|

Hif-1α/Hsf1/Hsp70 signaling pathway regulates redox homeostasis and apoptosis in large yellow croaker (<i>Larimichthys crocea</i>) under environmental hypoxia

Abstract: Oxygen is an essential molecule for animal respiration, growth, and survival. Unlike in terrestrial environments, contamination and climate change have led to the frequent occurrence of hypoxia in aquatic environments, thus impacting aquatic animal survival. However, the adaptative mechanisms underlying fish responses to environmental hypoxia remain largely unknown. Here, we used large yellow croaker ( Larimichthys crocea ) and large yellow croaker fry (LYCF) cells to investigate the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…In addition, both hypoxia and hypoxia-inducible factor-1alpha (HIF-1α) overexpression can inhibit the transcriptional activity of the AIF through targeting hypoxia-response element (HRE). AIF is also a target gene for HIF-1α in tumor cells ( 66 , 67 ). In recent years, research on tumor metabolism has become more comprehensive, and researchers have focused more on the correlation between mitochondria and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both hypoxia and hypoxia-inducible factor-1alpha (HIF-1α) overexpression can inhibit the transcriptional activity of the AIF through targeting hypoxia-response element (HRE). AIF is also a target gene for HIF-1α in tumor cells ( 66 , 67 ). In recent years, research on tumor metabolism has become more comprehensive, and researchers have focused more on the correlation between mitochondria and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mammalian cancers have indicated that the hypoxia sensor, HIF-1a (mammalian homolog of Drosophila Sima) activates HSF which in turn causes elevated expression of Hsps in different mammalian cancer cells (Agarwal and Ganesh, 2020; Baird et al, 2006; Luo et al, 2021; Tsuchida et al, 2014). However, our earlier study on lgl - yki OE clonal tumours in Drosophila (Singh et al, 2022) showed that their progression and transformation, and the expression of Hsp83 in them was HSF independent.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that inhibition of PI3K signalling can suppress HSF1 expression [44] and mutant p53, including R175H, R273H, R249S, and R282W, can promote HSF1 expression [45]. Moreover, HIF1‐α can bind to the HSF1 gene promoter to facilitate HSF1 transcription [46]. Clinical data show that 72% of HNSCC tumours have TP53 mutation and 14% of HNSCC tumours have PIK3CA mutation [1].…”
Section: Discussionmentioning
confidence: 99%